2007
DOI: 10.3233/bd-2007-26108
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Dormancy and Cancer Stem Cells: Implications for the Biology and Treatment of Breast Cancer Metastasis

Abstract: Breast cancer remains a leading cause of morbidity and mortality in women, mainly due to the propensity of primary breast tumors to metastasize to regional and distant sites. Metastatic spread after the removal of a primary tumor can be difficult to identify, creating uncertainty in patients with regards to possible cancer recurrence. This is a particular problem in breast cancer, exemplified by the fact that recurrence can take place after decades of apparent disease-free survival. The mechanisms underlying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
2
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(127 citation statements)
references
References 106 publications
3
118
2
4
Order By: Relevance
“…Recent evidence suggests that cancer stem cells, which are speculated to be resistant to cancer therapy, are a major cause of tumor relapse and metastasis (Dontu et al 2005, Allan et al 2006, Vaidya, 2007, Zhao et al 2008. It has also been suggested that important pathways regulating cell self-renewal and cell fate such as Wnt, C and CT K were considered as true CT-responsive genes that were clustered (standard correlation) based on gene expression between these two conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that cancer stem cells, which are speculated to be resistant to cancer therapy, are a major cause of tumor relapse and metastasis (Dontu et al 2005, Allan et al 2006, Vaidya, 2007, Zhao et al 2008. It has also been suggested that important pathways regulating cell self-renewal and cell fate such as Wnt, C and CT K were considered as true CT-responsive genes that were clustered (standard correlation) based on gene expression between these two conditions.…”
Section: Discussionmentioning
confidence: 99%
“…These three states of existence represent vastly different cancer biology with significant implications for detection, therapy, and patient outcomes. The factors that control the balance between dormancy and proliferation are poorly understood but are subject of much ongoing research [18][19][20][21].…”
Section: Dormancymentioning
confidence: 99%
“…In contrast, the self-renewal capacity of normal stem cells means these cells may be the only cells that are around long enough to accumulate the necessary mutations (Allan et al 2007 ) . Hence, stem or progenitor cells must be the initial targets for malignant transformation as the CSCs must be able to self-renew, and it would be more difficult for a mature cell to regain the ability to self-renew through genetic mutations.…”
Section: Rs öZenmentioning
confidence: 99%